Obesity alters the lung myeloid cell landscape to enhance breast cancer metastasis through IL5 and GM-CSF - Quail, Daniela F.; Olson, Oakley C.; Bhardwaj, Priya; Walsh, Logan A.; Akkari, Leila; Quick, Marsha L.; Chen, I-Chun; Wendel, Nils; Ben-Chetrit, Nir; Walker, Jeanne; Holt, Peter R.; Dannenberg, Andrew J.; et al. (Nature cell biology, 2017)
Obesity is associated with chronic, low-grade inflammation, which can disrupt homeostasis within tissue microenvironments. Given the correlation between obesity and relative risk of death from cancer, we investigated whether obesity-associated inflammation promotes metastatic progression. We demonstrate that obesity causes lung neutrophilia in otherwise normal mice, which is further exacerbated by the presence of a primary tumour. The increase in lung neutrophils translates to increased breast cancer metastasis to this site, in a GM-CSF- and IL5-dependent manner. Importantly, weight loss is sufficient to reverse this effect, and reduce serum levels of GM-CSF and IL5 in both mouse models and humans. Our data indicate that special consideration of the obese patient population is critical for effective management of cancer progression. Joyce and colleagues report that obesity promotes lung neutrophilia in mice, which in the presence of a primary breast tumour fosters metastasis to the lung in a manner dependent on GM-CSF and IL5.